English-Russian and Russian-English dictionary of exploration geophysics - Cherepovskiĭ, A. V. (EAGE Publications BV, 2008)
This is a substantially revised and enlarged version of Russian-English Dictionary of Exploration Geophysics. It contains about 15,500 terms used in seismic, electrical, gravity, magnetic and radiometric prospecting, logging and remote sensing. Also included are terms from geology, mathematics and computer science frequently used by geophysicists. --